2020
DOI: 10.1186/s12937-020-00647-4
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan modifies glycemic levels in people with metabolic syndrome and related disorders: meta-analysis with trial sequential analysis

Abstract: Background Chitosan supplementation has been shown to modulate glycemic levels; however, studies have reported conflicting results. The present meta-analysis with trial sequential analysis was conducted to verify the overall influence of chitosan on glycemic levels in patients with metabolic syndrome. Methods The PubMed, Cochrane library, and EMBASE databases were systematically searched for randomized controlled studies of chitosan intake and glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
(116 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, the glucose lowering effect of Se might be supported by other mechanisms, such as an acceleration of kidney glucose excretion in rats or stimulation of adipogenesis in adipocytes via stimulating serine/threonine kinases, including the p70 S6 kinase [ 47 ]. Also, Guo et al [ 48 ] reported that chitosan improves blood glucose levels and exerts its antidiabetic effect by upregulating the expression of glucose transporters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the glucose lowering effect of Se might be supported by other mechanisms, such as an acceleration of kidney glucose excretion in rats or stimulation of adipogenesis in adipocytes via stimulating serine/threonine kinases, including the p70 S6 kinase [ 47 ]. Also, Guo et al [ 48 ] reported that chitosan improves blood glucose levels and exerts its antidiabetic effect by upregulating the expression of glucose transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan-SeNPs have been shown to lower serum glucose concentrations by inhibiting the activity of α-amylase and α-glucosidase [ 57 ]. Furthermore, Guo et al [ 48 ] reported that chitosan exerts its antidiabetic effect by inhibiting the expression of intestinal α-amylase and α-glucosidase. Moreover, McCue et al [ 58 ] indicated that delaying carbohydrate absorption with Glib offers a prospective therapeutic approach for management of α-amylase and α-glucosidase activities in DM and may be beneficial for borderline diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to molecular weight≤16 kDa, COS is readily soluble in water and particularly useful for a series of industrial purposes. COS has already been proven to be effective in reducing body weight, lowering serum triglyceride and cholesterol levels, and limiting lipid accumulation in hepatocytes and adipose tissue (9,10). The currently reported anti-obesity mechanisms of COS mainly include inhibition of apolipoprotein B (ApoB) levels, PPAR-γ, bile acid secretion, pancreatic lipase production and reduction of serum ghrelin concomitant with increasing leptin (8).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is little information concerning the hypolipidemic and hypoglycemic effects of chitosan in type 2 diabetes with obesity. Guo et al (2020) have reported that the blood glucose level of patients with diabetes and obesity/overweight can be improved by supplementation with chitosan for at least 13 weeks [12]. Our previous study revealed that 7-week chitosan feeding did not affect blood glucose level but did decrease HOMA-IR index [13].…”
Section: Introductionmentioning
confidence: 99%